Peran Museum Perjuangan TNI dalam Merawat Peninggalan Karya Juang Prajurit di Kota Medan - Ginting, Trimahdalena; Monang, Sori; Devianty, Rina (Warisan: Journal of History and Cultural Heritage, 2021)
This article discusses the role of the Museum Perjuangan TNI in caring for the relics of the struggle of the Indonesian independence fighters in Medan and its surroundings. This article uses a historical research method with five steps, namely: topic selection, source collection, source criticism, interpretation, and historiography, with a qualitative approach. The main focus of this article is that the author wants to see the history of the establishment of the Museum Perjuangan TNI and the role it has in storing and caring for historical objects used by the fighters in Medan. Before becoming a museum, the building belonged to a Dutch insurance company named NV Levensverzekering Maatschappij Arnhem. After the Dutch surrender to Japan, the building was later converted into the headquarters of the Japanese army (Kementai). After being controlled by the Indonesians, this building was used as the office of the Commander of the Military Command (Pangdam) I-III. However, since October 5, 1996, this building was inaugurated as the TNI Struggle Museum by the Commander of the I/BB Regional Military Command, Major General (Mayjend). Sedaryanto. Currently the Museum Perjuangan TNI is located at Jalan KH. Zainul Arifin No. 8, Central Petisah Village, Medan City, North Sumatra Province. This museum acts as a place for education, tourism, and collective memory storage of the freedom fighters in Medan and its surroundings.